Meta-analysis reveals weak associations between intrinsic state and personality - Niemelä, Petri T.; Dingemanse, Niels J. (Proceedings of the Royal Society B: Biological Sciences, 2018)
Individual differences in behaviour characterize humans and animals alike. A hot field in behavioural ecology asks why this variation in ‘personality’ evolved. Theory posits that selection favours the integration of ‘intrinsic state’ and behaviour. Metabolism, hormones, energetic reserves and structural size have particularly been proposed as states covarying with behaviour among-individuals, either genetically or through plasticity integration. We conducted a meta-analysis estimating the amount of among-individual variation in behaviour attributable to variation in state. Our literature search showed that only 22% of the studies claiming to estimate individual-level associations between state and behaviour actually did so. Our meta-analysis revealed that relatively aggressive, bold, explorative and/or active individuals had relatively high metabolic rates, hormone levels, body weights and/or body sizes. The proportion of among-individual variation common to state and behaviour was nevertheless small (approx. 5%). This means that (i) adaptive explanations involving intrinsic states fail to explain much individual variation in behaviour, (ii) empiricists should consider nonlinear, additive or interactive effects of (multiple) intrinsic states, (iii) explanations not involving intrinsic states might be important, or (iv) empirical tests of state-dependent personality theory were inappropriate. Our meta-analysis highlights the importance of feedback between empiricists and theoreticians in the study of adaptive behavioural variation.